Prevalence of Hypertension and Its Risk Factors among Adults in Rural Community: A Cross-Sectional Study - Sangeeta Kori; Aarti G Sahasrabuddhe; Vinod K Arora (Medsci Publications, 2021)
Introduction: Hypertension is a chronic condition of concern due to its role in the causation of coronary heart disease, stroke and other vascular complications. Objectives of this study were to find out prevalence of hypertension among adults of rural community and association between hypertension and its risk factors. Methodology: Cross sectional community-based study was done with a sample of 501 adults between 18 to 60 years of age including both men (244) and women (257). A pretested semi-structured proforma was used collect data by trained doctors. Results: The overall prevalence of hypertension was found to be 32.13 %. Higher prevalence found among males (34%), age group 51-60 year (49.5%) and in class III SES (38.9%). Hypertension was found to be significantly associated with family history of hypertension (OR=2.41, CI= 1.50-3.80), smoking (OR= 1.78, CI=1.08-2.93), alcohol use (OR=1.8, CI=1.20-2.60), high salt intake (OR= 3.2, CI=1.80-5.45), junk food consumption (OR=2.40, CI=1.63-3.52), physical inactivity (OR=2.8, CI=1.90-4.14), overweight (OR=3.14, CI=2.11-4.66) and obesity (OR=3.78, CI=2.41-5.95). Conclusion: Increasing prevalence of hypertension in rural areas is major public health problem. Appropriate strategies are needed to create awareness regarding risk factors of hypertension.